Participatory Research on Child Maltreatment with Children and Adult Survivors Concepts, Ethics, and Methods - Roth, Maria; Alfandari, Ravit; Crous, Gemma (Emerald Studies in Child Centred Practice, 2023)
The ebook edition of this title is Open Access and freely available to read online. Childhood should be free of violence, and victims of childhood maltreatment should be entitled to participate as expert informants in research about these experiences. Placing children and adult survivors at the heart of research efforts on child maltreatment is critical to effective response and prevention measures in fighting this form of violence. Embedded in the European context, Participatory Research on Child Maltreatment with Children and Adult Survivors presents a mosaic of contexts, theories, and methods relating to children's and adult survivors' participation in research about their adverse experiences. Contributors demonstrate how research can mobilize children and adult survivors to become agents in constructing and disseminating reliable, evidence-based knowledge about child maltreatment. Enriching ongoing debates about ethical concerns and challenges of participatory research in the field of child maltreatment, this contribution to Emerald Studies in Child Centred Practice highlights the advantages that participation as a human right and as a valued endeavour of scientific knowledge accumulation can bring to communities of researchers and helping professionals. The authors of this book are members of a designated working group of the pan-European network on Multisectoral Responses to Child Abuse and Neglect in Europe (Euro-CAN), supported by the European Cooperation on Science Technology (COST Action 19106), that promote children's and child abuse survivors' participation in research on violence.